Application of Super-Twisting Sliding Mode Controllers in Direct Field-Oriented Control System of Six-Phase Induction Motor: Experimental Studies - Listwan Jacek (Power Electronics and Drives, 2018)
This paper presents the direct field-oriented control (DFOC) method of six-phase induction motor with the application of super-twisting sliding mode algorithm. The mathematical model of the six-phase induction motor has been described. The descriptions of the space vector modulation (SVM) method and the super-twisting algorithm have been presented. The DFOC method with super-twisting sliding mode controllers has been described. The experimental studies of the DFOC method with super-twisting controllers have been performed, and the results of these studies are presented and discussed.